2018
DOI: 10.25134/quagga.v10i01.872
|View full text |Cite
|
Sign up to set email alerts
|

Kesadaran Metakognisi Dan Keterampilan Memecahkan Masalah Mahasiswa Melalui Pembelajaran Berbasis Masalah Dengan Penugasan Individu

Abstract: AbstrakHasil penelitian sebelumnya menunjukkan bahawa mahasiswa telah memiliki keterampilan memecahkan masalah baik namun masih terdapat kelemahan pada keterampilan menentukan solusi terbaik dan melakukan evaluasi, hal tersebut diasumsikan juga bahwa kesadaran metakognisi mahasiswa masih rendah. Tujuan dari penelitian ini adalah untuk menganalisis peningkatan keterampilan memecahkan masalah dan kesadarn metakognisi serta hubungannya� melalui pembelajaran berbasis masalah dengan penugasan individu. Hasil peneli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Students can describe the correlation between conceptual and methodology to answer the problems. Metacognition awareness can help students solve problems through effective design, which involves identifying problems, understanding problems that need to be solved, and understanding practical strategies [21]. This, of course, needs to be accommodated by applying laboratory learning in the form of designing experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Students can describe the correlation between conceptual and methodology to answer the problems. Metacognition awareness can help students solve problems through effective design, which involves identifying problems, understanding problems that need to be solved, and understanding practical strategies [21]. This, of course, needs to be accommodated by applying laboratory learning in the form of designing experiments.…”
Section: Resultsmentioning
confidence: 99%
“…This is necessary for students to study all the new knowledge received in the PAI course process. The readiness of students' cognitive thinking to carry out the process of selfregulation (self-regulated) has been pointed out in Maulyda, Budiharjo, Erfan, and Radha's (2020) research which concluded that self-refl ection in the form of metacognitive thinking actions is needed by students during online lectures which needs to be developed as awareness from within oneself (Widiantie & Handayani, 2018) as an eff ort to solve problems faced by individuals through a self-regulated learning process. Thus, the authors can state that the learning design of Islamic course implemented at MU leads to the development of students' self-regulated learning and regulatory abilities through three main indicators owned by each student: creativity, ability to think critically, and self-regulation (Baptist et al, 2021;Huang, Li, Poitras, & Lajoie, 2021;Setyaningsih & Djukri, 2020)…”
Section: Finding and Discussionmentioning
confidence: 99%
“…The problem solver, in this case, the students are required to identify an unclear and unstructured problem. At this stage, students' problem-solving skills are empowered because students are focused on solving the problems they find (Widiantie & Lismaya, 2017). Identifying the problem is a stage that warrants further theoretical search to produce a potential model for solving the problem.…”
Section: Calculationmentioning
confidence: 99%